2021
DOI: 10.1111/ppl.13606
|View full text |Cite
|
Sign up to set email alerts
|

Joint GWAS and WGCNA uncover the genetic control of calcium accumulation under salt treatment in maize seedlings

Abstract: Soil salinization is an important factor threatening the yield and quality of maize. Ca2+ plays a considerable role in regulating plant growth under salt stress. Herein, we examined the shoot Ca2+ concentrations, root Ca2+ concentrations, and transport coefficients of seedlings in an association panel composed of 305 maize inbred lines under normal and salt conditions. A genome‐wide association study was conducted by using the investigated phenotypes and 46,408 single‐nucleotide polymorphisms of the panel. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 95 publications
(138 reference statements)
2
10
0
Order By: Relevance
“…Similar to our observations, previous reports have also shown that salinity negatively affects seedling-related traits [ 29 32 ]. In a conclusion, salt stress remarkably limits wheat seedling growth, as previously reported by Liang et al [ 9 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to our observations, previous reports have also shown that salinity negatively affects seedling-related traits [ 29 32 ]. In a conclusion, salt stress remarkably limits wheat seedling growth, as previously reported by Liang et al [ 9 ].…”
Section: Discussionsupporting
confidence: 85%
“…In-depth phenotyping is a key part of a GWAS procedure [ 29 ]. Herein, a total of 25 seedling-linked traits were evaluated that have been previously employed for QTL mapping of salinity tolerance at the seedling stage in cotton, rice, and maize [ 7 , 9 , 10 ]. Similar to our observations, previous reports have also shown that salinity negatively affects seedling-related traits [ 29 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistical analysis was performed using SPSS25 software. The broad-sense heritability ( H 2 ) was calculated as follows [ 39 ]: H 2 = σ G 2 /σ P 2 , σ G 2 = (MSG-MSE)/rep, σ P 2 = (MSG-MSE)/rep + MSE. Herein, σ G 2 , σ P 2 , MSG, MSE, and rep represent genotypic variance, phenotypic variance, mean square of genotype, mean square of error, and number of replicates, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is based on the linkage disequilibrium (LD) of molecular markers. Using a GWAS, 544 initial candidate genes affecting Ca 2+ concentrations were detected in maize seedlings under salt stress [ 4 ]. Luo et al identified 57 loci significantly associated with maize salt tolerance using a GWAS.…”
Section: Introductionmentioning
confidence: 99%